Acute ischemic stroke and the acute need for expansion of stroke teams and their membership. Issue 3 (18th February 2021) - Andress, Krystof; Moliterno, David J.
Key Points: This database review of patients with acute ischemic stroke (AIS) receiving endovascular stroke therapy (EST) revealed an encouraging increase in the number of procedures performed between 2015 and 2019. However, given the likely low proportion of patients with large‐vessel‐occlusion AIS who receive EST, there is still a significant unmet need. Given the urgent nature of AIS and lack of neurointerventionalists at some community hospitals, creation and expansion of stroke teams to include appropriately trained interventional cardiologists could improve time‐to‐treatment metrics and outcomes.